A polyimide binder, electrode sheet, battery, battery pack, and electric device

CN122958981APending Publication Date: 2026-10-23BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510496095.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,在聚酰亚胺粘结剂的合成过程中,单体转化不完全,存在未反应的单体,而未反应的单体在电解液中溶出形成溶出物,这些溶出物在电极表面或界面处形成沉积层,增加界面阻抗,阻碍锂离子的传输

Benefits of technology

[0054]本发明提供一种聚酰亚胺粘结剂、电极片、电池、电池组及用电设备,聚酰亚胺粘结剂的制备方法包括如下步骤:(1)将酯单体在引发剂作用下进行第一反应,得到羟基封端的聚酯段前驱体;(2)将羟基封端的聚酯段前驱体和二异氰酸酯混合,进行第二反应,得到中间产物;(3)将二酸酐单体加入中间产物,进行第三反应,得到聚酰亚胺粘结剂。通过调控第一反应的温度≥120℃,第一反应的时间≥5h,使酯单体充分参与第一反应,有效提高酯单体的转化率,减少未反应的酯单体的含量,避免未反应的单体在电解液中的溶出,促进锂离子的传输,并减少溶出物与电解液或电极材料发生化学反应,保护电解液或电极的活性物质,从而提升电池的循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a polyimide binder, an electrode sheet, a battery, a battery pack and an electric device. A preparation method of the polyimide binder comprises the following steps: performing a first reaction on an ester monomer under the action of an initiator to obtain a hydroxyl-terminated polyester segment precursor; subsequently mixing the hydroxyl-terminated polyester segment precursor and a diisocyanate to perform a second reaction to obtain an intermediate product; and then adding a diacid anhydride monomer into the intermediate product to perform a third reaction to obtain the polyimide binder. In the first reaction, the reaction temperature is greater than or equal to 120 DEG C, and the reaction time is greater than or equal to 5 h. The application can improve the conversion rate of the ester monomer, thereby improving the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery material technology, specifically relating to a polyimide binder, electrode sheet, battery, battery pack, and electrical equipment. Background Technology

[0002] Polyimide binders are widely used in lithium-ion batteries due to their excellent chemical stability, thermal stability, mechanical strength, and electrical insulation. However, during the synthesis of polyimide binders, monomer conversion is incomplete, resulting in unreacted monomers. These unreacted monomers dissolve in the electrolyte, forming exudates. These exudates form deposits on the electrode surface or interface, increasing interfacial impedance and hindering lithium-ion transport. Furthermore, unreacted monomers react chemically with the electrolyte or electrode materials, consuming the active materials in the electrolyte or electrode, leading to battery capacity decay and affecting the battery's cycle performance. Summary of the Invention

[0003] This invention provides a polyimide binder, electrode sheet, battery, battery pack, and electrical equipment, which can effectively improve the conversion rate of ester monomers and reduce the content of unreacted ester monomers, thereby improving the cycle performance of the battery.

[0004] In one aspect, the present invention provides a method for preparing a polyimide adhesive, comprising the following steps:

[0005] (1) The ester monomer is subjected to a first reaction under the action of an initiator to obtain a hydroxyl-terminated polyester precursor;

[0006] (2) The hydroxyl-terminated polyester precursor and diisocyanate are mixed and a second reaction is carried out to obtain an intermediate product.

[0007] (3) Add the dianhydride monomer to the intermediate product to carry out the third reaction to obtain the polyimide binder;

[0008] In the first reaction, the reaction temperature is ≥120℃ and the reaction time is ≥5h.

[0009] According to one embodiment of the present invention, in the first reaction, the reaction temperature is 120-180°C and the reaction time is 5-10 h.

[0010] According to one embodiment of the present invention, in the second reaction, the reaction temperature is 70-90°C and the reaction time is 1-15 h.

[0011] According to one embodiment of the present invention, in the third reaction, the reaction temperature is 40-60°C and the reaction time is 1-15 h.

[0012] According to one embodiment of the present invention, the molar ratio of the initiator to the ester monomer is 1:(5-100).

[0013] According to one embodiment of the present invention, the molar ratio of the diisocyanate to the ester monomer is (0.1-50):1.

[0014] According to one embodiment of the present invention, the molar ratio of the dianhydride monomer to the ester monomer is (0.07-1.32):1.

[0015] According to one embodiment of the present invention, the ester monomer includes a cyclic ester monomer, preferably the cyclic ester monomer includes lactones and / or lactones.

[0016] According to one embodiment of the present invention, the initiator includes a small molecule diol initiator and / or a small molecule diamine initiator.

[0017] According to one embodiment of the present invention, the lactone has the structure shown in Formula A:

[0018]

[0019] R7 is a straight-chain alkyl group or a branched alkyl group having 1 to 12 carbon atoms.

[0020] The lactone has the structure shown in Formula B:

[0021]

[0022] R8 and R9 are each independently selected from straight-chain alkyl groups having 1 to 12 carbon atoms or branched alkyl groups.

[0023] According to one embodiment of the present invention, the lactone has the structure shown in formula C:

[0024]

[0025] Where a1, b1, and c1 are the number of methylene groups at the corresponding positions of the monomer, a1 is an integer from 0 to 11, b1 is an integer from 0 to 12, and c1 is an integer from 0 to 12.

[0026] The lactone has the structure shown in formula D:

[0027]

[0028] Where a2 and b2 are the number of methylene groups at the corresponding positions of the monomer, with a2 being an integer from 1 to 10 and b2 being an integer from 1 to 10.

[0029] According to one embodiment of the present invention, the diisocyanate is selected from the structures shown in formulas XII-1 to XII-16:

[0030]

[0031] According to one embodiment of the present invention, the dianhydride monomer is selected from the structures shown in formulas X-1 to X-9:

[0032]

[0033] According to one embodiment of the present invention, the process of adding dianhydride monomer to the intermediate product and carrying out a third reaction to obtain polyimide adhesive includes: adding dianhydride monomer to the intermediate product and carrying out a third reaction to obtain polyimide solution; placing the polyimide solution in an antisolvent for precipitation and separation to obtain a solid product, wherein the solid product is the polyimide adhesive.

[0034] The antisolvent includes one or more of ethanol, propanol, and isopropanol. In another aspect, the present invention provides a polyimide adhesive prepared by the above-described preparation method.

[0035] According to one embodiment of the present invention, the polyimide adhesive has a structure as shown in formula E1 or formula E2:

[0036]

[0037] Where x is an integer from 5 to 500, and y is an integer from 0 to 500;

[0038] R1 is selected from substituted or unsubstituted aryl groups, or substituted or unsubstituted biaryl groups;

[0039] Preferably, the substituted or unsubstituted biaryl group has the structure shown in formula F:

[0040]

[0041] R 10 and R 11 Each independently represents a monosubstituted to the maximum permissible substituent, and R 10 and R 11 Each is independently selected from hydrogen, substituted or unsubstituted alkyl, or carboxyl, and L2 is selected from one or more of single bond, substituted or unsubstituted alkyl, carbonyl, ester, oxygen, sulfone, and amide.

[0042] R2 is selected from the structures shown in equation G and / or equation H as follows:

[0043]

[0044] R4 is selected from straight-chain alkyl or branched alkyl with 1 to 18 carbon atoms, and x1 is an integer from 10 to 25. Preferably, R4 is selected from straight-chain alkyl or branched alkyl with 4 to 8 carbon atoms.

[0045]

[0046] R5 and R6 are each independently selected from straight-chain alkyl groups having 1 to 12 carbon atoms or branched alkyl groups, and y1 is an integer from 10 to 25. Preferably, R5 and R6 are each independently selected from straight-chain alkyl groups having 1 to 5 carbon atoms or branched alkyl groups.

[0047] R3 is selected from the structures shown in equations XI-1 to XI-16 below:

[0048]

[0049] In another aspect, the present invention provides an electrode sheet comprising an electrode coating, the electrode coating comprising the above-described polyimide binder, or a polyimide binder prepared according to the above-described method for preparing the polyimide binder.

[0050] According to one embodiment of the present invention, the electrode sheet includes a positive electrode sheet.

[0051] In another aspect, the present invention provides a battery comprising the electrode sheets described above.

[0052] In another aspect, the present invention provides a battery pack comprising at least two batteries as described above that are interconnected.

[0053] In another aspect, the present invention provides an electrical device comprising the battery or battery pack described above.

[0054] This invention provides a polyimide binder, electrode sheet, battery, battery pack, and electrical equipment. The preparation method of the polyimide binder includes the following steps: (1) ester monomers undergo a first reaction under the action of an initiator to obtain a hydroxyl-terminated polyester precursor; (2) the hydroxyl-terminated polyester precursor and diisocyanate are mixed and subjected to a second reaction to obtain an intermediate product; (3) dianhydride monomers are added to the intermediate product and subjected to a third reaction to obtain the polyimide binder. By controlling the temperature of the first reaction to ≥120℃ and the time of the first reaction to ≥5h, the ester monomers are fully involved in the first reaction, effectively improving the conversion rate of the ester monomers, reducing the content of unreacted ester monomers, avoiding the dissolution of unreacted monomers in the electrolyte, promoting the transport of lithium ions, and reducing the chemical reaction between the dissolved substances and the electrolyte or electrode materials, protecting the active materials of the electrolyte or electrode, thereby improving the cycle performance of the battery. Detailed Implementation

[0055] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0056] Polyimide binders are widely used in lithium-ion batteries due to their excellent chemical stability, thermal stability, mechanical strength, and electrical insulation. However, during the synthesis of polyimide binders, monomer conversion is incomplete, resulting in unreacted monomers. These unreacted monomers dissolve in the electrolyte, forming exudates. These exudates form deposits on the electrode surface or interface, increasing interfacial impedance and hindering lithium-ion transport. Furthermore, unreacted monomers react chemically with the electrolyte or electrode materials, consuming the active materials of the electrolyte or electrode, leading to battery capacity decay and affecting the battery's cycle performance. According to the inventors' research, by combining aromatic hard segments and polyester soft segments, the adhesion, mechanical properties, and flexibility of polyimide binders can be improved, while also improving the processing performance of polyimide binders when used in electrode sheet fabrication, thereby enhancing battery safety, cycle stability, and cycle life. Through evaluation and use of this polyimide binder, the inventors found that the content of exudates varies when the polyimide binder is immersed in the electrolyte under different synthesis processes. Structural analysis of the leachate revealed that the conversion rate of ester monomers did not reach 100% during the synthesis of the polyester precursor in the original process, and the mass percentage of the leachate in the electrolyte was about 5%. The long-term presence of this leachate in the battery will reduce the battery's cycle performance.

[0057] In view of this, embodiments of the present invention provide a method for preparing a polyimide adhesive, comprising the following steps:

[0058] (1) The ester monomer is subjected to a first reaction under the action of an initiator to obtain a hydroxyl-terminated polyester precursor;

[0059] (2) The hydroxyl-terminated polyester precursor and diisocyanate are mixed and subjected to a second reaction to obtain an intermediate product.

[0060] (3) Add the dianhydride monomer to the intermediate product to carry out the third reaction to obtain the polyimide binder;

[0061] In the first reaction, the reaction temperature is ≥120℃ and the reaction time is ≥5h.

[0062] In the first reaction under the action of an initiator, the ester monomer undergoes a ring-opening polymerization reaction to generate a hydroxyl-terminated polyester precursor. Subsequently, the hydroxyl-terminated polyester precursor undergoes a second reaction with diisocyanate (i.e., diisocyanate capping agent) to obtain an intermediate product containing an isocyanate-terminated polyester precursor. Then, dianhydride monomer is added to the intermediate product, and the dianhydride monomer undergoes a third reaction with the isocyanate-terminated polyester precursor in the intermediate product to remove carbon dioxide, yielding a polyimide binder. By controlling the temperature of the first reaction to ≥120℃ and the reaction time to ≥5h, the ester monomer fully participates in the first reaction, improving the conversion rate of the ester monomer, effectively reducing the content of unreacted ester monomer, preventing the dissolution of unreacted monomer in the electrolyte, promoting lithium-ion transport, and reducing chemical reactions between the dissolved substances and the electrolyte or electrode materials, thus protecting the active materials of the electrolyte or electrode and improving the cycle performance of the battery.

[0063] For example, in the first reaction, the reaction temperature can be 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃ or 200℃, etc., and the reaction time can be 5h, 8h, 13h or 15h, etc.

[0064] It is understandable that in the above-mentioned method for preparing polyimide adhesives, in order to make the first, second and third reactions more complete, the reaction system can be mixed, such as by using a stirrer.

[0065] In some embodiments, in step (1), the ester monomer undergoes a first reaction in a solvent under the action of an initiator. The present invention does not specifically limit the type and amount of solvent; the solvent can be selected according to the subsequent preparation of the electrode paste. For example, the solvent includes at least one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc), tetramethylurea, 1,3-dimethyl-2-imidazolinone acetone, butanone (MEK), tetrahydrofuran (THF), ethanol, isopropanol, ethylene glycol monomethyl ether, diethylene glycol dimethyl ether, ethylene carbonate, and propylene carbonate. In specific implementations, the mass percentage of the ester monomer in the solvent is 1% to 10%.

[0066] In some embodiments, step (3), after adding the dianhydride monomer to the intermediate product and carrying out the third reaction, further includes a drying process to obtain the polyimide binder. The drying process can be any conventional drying step capable of removing the solvent, and is not particularly limited thereto. For example, evaporation, vacuum distillation, or baking can be used for the drying process.

[0067] In this embodiment of the invention, the conversion rate of ester monomers can be determined by gas chromatography (GC). Specifically, n-dodecane is used as an internal standard and methanol is used as a solvent to prepare an internal standard solution. The prepared polyimide binder is dissolved in methanol, and the internal standard solution is added. The solution is filtered using a PTFE filter membrane, and the filtrate is collected as the target analyte stock solution. Using one of NMP, p-phenyl diisocyanate, or terephthalic anhydride as the standard solute and methanol as the solvent, standards with concentrations of 0.1 μg / mL, 0.5 μg / mL, 1 μg / mL, 5 μg / mL, and 10 μg / mL are prepared. An equal amount of internal standard (n-dodecane) is added to each concentration of standard. The sample preparation steps (taking 1 μg / mL as an example): Take 1 mL of the sample stock solution and dilute it with methanol to 100 mL to obtain a 10 μg / mL intermediate solution. Mix 10 μL of intermediate solution, 90 μL of methanol, and 100 μL of internal standard solution to obtain a total volume of 1 mL of test sample (wherein, the sample concentration is 1 μg / mL and the internal standard concentration is 1 μg / mL). Analyze the test sample and standards using gas chromatography, recording the peak area of ​​each component and performing data analysis using the internal standard method. For each standard and sample, calculate the ratio (R) of the sample peak area to the internal standard peak area; fit a linear equation with the standard concentration (X) as the x-axis and the R value as the y-axis; substitute the R value of the sample into the fitted linear equation to deduce the sample concentration. Ester monomer conversion rate = (total ester monomer mass - residual ester monomer mass) / total ester monomer mass, where the residual ester monomer mass is calculated from the sample concentration measured by GC. In some embodiments, the reaction temperature in the first reaction is 120–180 °C, and the reaction time is 5–10 h, which can further improve the ester monomer conversion rate and improve the battery cycle performance.

[0068] For example, in the first reaction, the reaction temperature can be 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃, 175℃ or 180℃, etc., and the reaction time can be 5h, 6h, 7h, 8h, 9h or 10h, etc.

[0069] In some embodiments, the reaction temperature in the second reaction is 70–90°C and the reaction time is 1–15 h, so that the hydroxyl and isocyanate groups can react fully and the occurrence of side reactions can be reduced.

[0070] For example, in the second reaction, the reaction temperature can be 70℃, 75℃, 80℃, 85℃ or 90℃, etc., and the reaction time can be 1h, 3h, 5h, 7h, 9h, 11h, 13h or 15h, etc.

[0071] In some embodiments, the reaction temperature in the third reaction is 40–60°C and the reaction time is 1–15 h, which can promote the full third reaction between the dianhydride monomer and the diisocyanate and isocyanate-terminated polyester precursor to obtain a high-purity polyimide binder.

[0072] For example, in the third reaction, the reaction temperature can be 40℃, 45℃, 50℃, 55℃ or 60℃, etc., and the reaction time can be 1h, 3h, 5h, 7h, 9h, 11h, 13h or 15h, etc.

[0073] In some embodiments, the molar ratio of initiator to ester monomer is 1:(5-100), which can improve the reaction efficiency of the first reaction while reducing the residue of unreacted ester monomer, thereby further improving the conversion rate of ester monomer.

[0074] For example, the molar ratio of the initiator to the ester monomer can be 1:5, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100, etc.

[0075] In some embodiments, the molar ratio of diisocyanate to ester monomer is (0.1-50):1, which is beneficial to improve the adhesion of polyimide adhesive, giving the polyimide adhesive both good mechanical properties and flexibility.

[0076] For example, the molar ratio of diisocyanate to ester monomer can be 0.1, 0.2, 0.3, 0.4, 0.5, 1, 2, 5, 10, 20, 30, 40 or 50, which is beneficial to improving the stiffness, strength, thermal stability and chemical stability of polyimide adhesives.

[0077] In some embodiments, the molar ratio of diisocyanate to ester monomer is (3-50):1, which can further improve the adhesion of polyimide adhesive, giving the polyimide adhesive both better mechanical properties and flexibility.

[0078] For example, the molar ratio of diisocyanate to ester monomer can be 3:1, 5:1, 7:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1 or 50:1, etc.

[0079] In some embodiments, the molar ratio of dianhydride monomer to ester monomer is (0.07-1.32):1, which is beneficial to further improve the stiffness, strength, thermal stability and chemical stability of the polyimide binder.

[0080] For example, the molar ratio of dianhydride monomer to ester monomer can be 0.07:1, 0.1:1, 0.3:1, 0.5:1, 0.7:1, 0.9:1, 1.1:1, 1.3:1, or 1.32:1.

[0081] In some embodiments, the ester monomer includes a cyclic ester monomer, which typically exhibits higher reactivity, thus improving the efficiency and rate of the first reaction and increasing the conversion rate of the ester monomer. Simultaneously, cyclic ester monomers generally produce fewer byproducts during polymerization, contributing to improved purity of the hydroxyl-terminated polyester precursor. Further, the cyclic ester monomer includes lactones and / or lactides; that is, the ester monomer can be solely a lactone monomer, or solely a lactide monomer, or it can simultaneously include both lactone and lactide monomers. This invention does not impose a specific limitation on the molar ratio of these two monomers; the ratio can be selected based on actual conditions.

[0082] The lactone monomer of this invention has the structure shown in Formula A:

[0083]

[0084] Wherein, R7 is selected from straight-chain alkyl or branched alkyl. Specifically, R7 is a straight-chain alkyl or branched alkyl with 1 to 12 carbon atoms (such as an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12). Preferably, R7 is a straight-chain alkyl or branched alkyl with 4 to 6 carbon atoms (such as an integer number of carbon atoms of 4, 5 or 6). For example, when R7 is a straight-chain alkyl group, it includes, but is not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.; when R7 is a branched alkyl group, it includes, but is not limited to, isopropyl, tert-butyl, isobutyl, sec-butyl, neopentyl, isopentyl, tert-pentyl, 3-methylbutyl, 2-methylbutyl, 2,2-dimethylpropyl, 2-methylpentyl, 3-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,2,3-trimethylbutyl, 2,2,4-trimethylpentyl, 2,4-dimethylpentyl, 3,3-dimethylbutyl, 3-methylhexyl The lactone monomers, such as 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylhexyl, 2,2,5-trimethylhexyl, and 2,2,4-trimethylpentyl, possess excellent chemical stability, interfacial compatibility, flexibility, and ductility. Introducing these lactone monomers into the polyimide binder structure through ring-opening polymerization improves the interfacial compatibility between the polyimide binder and the electrode material, enhances the adhesion performance of the polyimide binder, and simultaneously improves the chemical stability and mechanical properties of the polyimide binder. This enables the polyimide binder to resist electrolyte erosion, reduces mechanical stress and crack formation in the electrode during charging and discharging, thereby improving the long-term cycle life of the battery.

[0085] The lactone monomer of this invention has the structure shown in Formula B:

[0086]

[0087] R8 and R9 are each independently selected from straight-chain alkyl groups or branched alkyl groups with 1 to 12 carbon atoms (such as integers of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 carbon atoms). Preferably, R8 and R9 are each independently selected from straight-chain alkyl groups or branched alkyl groups with 4 to 6 carbon atoms (such as integers of 4, 5 or 6 carbon atoms). For example, when R8 and R9 are independently selected from straight-chain alkyl groups, they include, but are not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.; when R8 and R9 are independently selected from branched alkyl groups, they include, but are not limited to, isopropyl, tert-butyl, isobutyl, sec-butyl, neopentyl, isopentyl, tert-pentyl, 3-methylbutyl, 2-methylbutyl, 2,2-dimethylpropyl, 2-methylpentyl, 3-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,2,3-trimethylbutyl, 2,2,4-trimethylbutyl... Lactoyl, 2,4-dimethylpentyl, 3,3-dimethylbutyl, 3-methylhexyl, 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylhexyl, 2,2,5-trimethylhexyl, 2,2,4-trimethylpentyl, etc., are lactone monomers that possess excellent chemical stability, mechanical properties, interfacial compatibility, and thermal stability. Lactoyl monomers are introduced into the polyimide binder structure through ring-opening polymerization, which helps to improve the interfacial compatibility between the polyimide binder and the electrode material, enhance the adhesion performance of the polyimide binder, and improve the thermal and chemical stability of the polyimide binder, thereby improving the long-term cycle life of the battery.

[0088] Furthermore, the lactone monomers in the embodiments of the present invention have the structure shown in Formula C:

[0089]

[0090] Where a1, b1, and c1 are the number of methylene groups at the corresponding positions of the monomer, with a1 being an integer from 0 to 11; b1 being an integer from 0 to 12; and c1 being an integer from 0 to 12.

[0091] For example, the lactone monomers in the embodiments of the present invention have a structure as shown in Formula D:

[0092]

[0093] Where a2 and b2 are the number of methylene groups at the corresponding positions of the monomer, with a2 being an integer from 1 to 10; and b2 being an integer from 1 to 10.

[0094] For example, the lactone monomers in the embodiments of the present invention include, but are not limited to, one or more of caprolactone, valproic acid, butyrolactone, and nonanolide (γ-nonanolide); the lactide monomers in the embodiments of the present invention include, but are not limited to, one or more of lactic acid (lactide), glycolide, and di-n-butyl glycolide, which are beneficial to better improve the interfacial compatibility between the polyimide binder and the electrode material, enhance the adhesion performance of the polyimide binder, and improve the thermal and chemical stability of the polyimide binder, thereby further improving the long-term cycle life of the battery.

[0095] In some embodiments, the initiator includes at least one of a glycol initiator and a diamine initiator. It should be noted that regardless of whether a glycol initiator or a diamine initiator is used, the resulting hydroxyl-terminated polyester precursor will have hydroxyl groups as end groups.

[0096] In one specific embodiment, the small molecule diol initiator includes, but is not limited to, one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, triethylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, cyclohexanediol, and glycerol. In a specific implementation, ethylene glycol can be used as the small molecule diol initiator.

[0097] In one specific embodiment, the small molecule diamine initiator includes, but is not limited to, one or more of the following: ethylenediamine, propylenediamine, butyldiamine (1,4-butyldiamine), pentanediamine (1,5-pentanediamine), hexanediamine (1,6-hexanediamine), isophorone diamine (IPDA), phenyl dimethyl diamine (such as m-phenylenediamine and p-phenylenediamine), cyclohexane diamine (such as 1,2-cyclohexanediamine and 1,4-cyclohexanediamine), diethyltoluene diamine (DETDA), and dimethylthiotoluene diamine (DMTDA).

[0098] The diisocyanates of the present invention comprise compounds with two isocyanate structures. The diisocyanates of the present invention can be selected from the structures shown in formulas XII-1 to XII-16 below:

[0099]

[0100] In this embodiment of the invention, formula XII-1 can be a structure as shown in formula 5:

[0101]

[0102] Equation XII-2 can be a structure as shown in Equation 6:

[0103]

[0104] In some embodiments, the diisocyanate includes, but is not limited to, one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), naphthalene diisocyanate (NDI), and cyclohexane diisocyanate (CHDI).

[0105] This invention does not impose any particular limitation on the type of dianhydride monomer, as long as it can provide aromatic hard segments for the polyimide binder. For example, dianhydride monomers include, but are not limited to, the structures shown in formulas X-1 to X-9 below:

[0106]

[0107] In some embodiments, the process of adding dianhydride monomers to an intermediate product and carrying out a third reaction to obtain a polyimide binder includes: adding dianhydride monomers to an intermediate product and carrying out a third reaction to obtain a polyimide solution; placing the polyimide solution in an antisolvent for precipitation; and separating the solid product (i.e., the polyimide binder) and a supernatant. Precipitating the polyimide solution in an antisolvent helps remove residual ester monomers from the polyimide solution; the antisolvent is a solvent that can reduce the solubility of the solute (i.e., polyimide), causing the polyimide to precipitate from the solvent. Antisolvents include one or more of ethanol, propanol, and isopropanol. This further facilitates the removal of residual ester monomers from the polyimide solution.

[0108] Furthermore, the volume ratio of antisolvent to polyimide solution is (2-20):1, and the precipitation time is 0.5-2h, which can better remove residual ester monomers in polyimide solution.

[0109] For example, the volume ratio of solvent to polyimide liquid can be 2:1, 3:1, 4:1, 5:1, 6:1, 8:1, 10:1, 14:1, 16:1, 18:1 or 20:1, etc.

[0110] For example, the precipitation time can be 0.5h, 1h, 1.5h or 2h, etc.

[0111] According to the inventors' research, when polyimide adhesive is prepared using polyimide solution, the mass percentage of dissolved substances in the electrolyte is about 5%. When the polyimide solution is placed in water for precipitation and the polyimide adhesive is separated, the mass percentage of dissolved substances in the electrolyte is still about 5%. However, after using an anti-solvent to precipitate the polyimide solution, the mass percentage of dissolved substances in the electrolyte can be reduced to 1.5%.

[0112] On the other hand, embodiments of the present invention provide a polyimide binder prepared by the above-described preparation method. This polyimide binder exhibits enhanced chemical stability in the electrolyte, preventing adverse chemical reactions between residual ester monomers and the electrolyte or electrode materials, protecting the active materials of the battery, and thereby improving the battery's cycle performance.

[0113] In this embodiment of the invention, the polyimide adhesive has the structure shown in Formula E1 or Formula E2:

[0114]

[0115]

[0116] Where x is an integer between 5 and 500, and y is an integer between 0 and 500. R1 is the first aromatic hard segment, R2 is the polyester soft segment, and R3 is the second aromatic hard segment. x is a repeating unit of the polyimide binder. The number of repeating units of the polyimide adhesive, y. The quantity.

[0117] For example, x can be an integer such as 5, 10, 50, 100, 150, 200, 250, 300, 350, 400, 450, or 500.

[0118] For example, y can be an integer such as 0, 5, 10, 50, 100, 150, 200, 250, 300, 350, 400, 450 or 500.

[0119] Furthermore, x is preferably 10-100, which is beneficial for further improving the cycle performance of the battery.

[0120] For example, x can be an integer such as 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100.

[0121] Furthermore, y is preferably 10-100, which is beneficial to further improve the cycle performance of the battery.

[0122] For example, x can be an integer such as 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100.

[0123] In this embodiment of the invention, the structure of the polyimide adhesive can be adjusted by regulating the molar ratio of diisocyanate and dianhydride monomers. When the molar ratio of diisocyanate and dianhydride monomers is 1:1, the polyimide adhesive has the structure shown in Formula E2. When the molar ratio of diisocyanate and dianhydride monomers is greater than 1:1, the polyimide adhesive has the structure shown in Formula E1.

[0124] In this embodiment of the invention, x and y in formula E1 and x in formula E2 can be controlled by conventional methods of controlling the number of repeating units in polymer segments or polymers. For example, the number x of repeating units can be controlled by adjusting conditions such as the molar ratio of the initiator to the ester monomer, the molar ratio of the diisocyanate to the ester monomer, and the molar ratio of the dianhydride monomer to the ester monomer used to form the structure shown in formula E2. The number x and y of repeating units can be controlled by adjusting conditions such as the molar ratio of the initiator to the ester monomer, the molar ratio of the diisocyanate to the ester monomer, and the molar ratio of the dianhydride monomer to the ester monomer used to form the structure shown in formula E1.

[0125] Furthermore, in embodiments of the present invention, x in formula E1 and y in formula E2 can be determined by conventional testing methods for the number of repeating units in polymer chains or polymers. For example, after obtaining the polyimide binder, the polyimide binder is degraded to obtain various monomers, initiators, and other components used to form the polyimide binder, and x in formula E1 or y in formula E2 is determined by high performance gas chromatography.

[0126] R1 is selected from substituted or unsubstituted aryl groups, or substituted or unsubstituted biaryl groups;

[0127] Preferably, the substituted or unsubstituted biaryl group has the structure shown in formula F:

[0128]

[0129] R 10 and R 11 Each independently represents a monosubstituted to the maximum permissible substituent, and R 10 and R 11 Each group is independently selected from hydrogen, substituted or unsubstituted alkyl, or carboxyl, and L2 is selected from one or more of single bond, substituted or unsubstituted alkyl, carbonyl, ester, oxygen, sulfone, and amide.

[0130] Specifically, L2 can be one or more of the following: alkyl group with 1 to 12 carbon atoms (e.g., an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12); carbonyl group with 1 to 12 carbon atoms (e.g., an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12); ester group with 1 to 12 carbon atoms (e.g., an oxygen group); sulfone group with 1 to 12 carbon atoms (e.g., an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12); amide group with 1 to 12 carbon atoms (e.g., an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12); amide group with 1 to 12 carbon atoms (e.g., an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12). For example, when L2 is an alkyl group, it includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, and n-hexyl; when L2 is a carbonyl group, it includes, but is not limited to, aldehyde and ketone groups; when L2 is an ester group, it includes, but is not limited to, methoxycarbonyl, ethoxycarbonyl, propoxycarbonyl, and butoxycarbonyl; when L2 is a sulfone group, it includes, but is not limited to, dimethyl sulfone, diethyl sulfone, and methyl ethyl sulfone; when L2 is an amide group, it includes, but is not limited to, carbamoyl, acetamido, N-methylcarbamoyl, and N,N-dimethylcarbamoyl. Furthermore, any hydrogen atom in L2 can be replaced by a halogen atom, such as a fluorine atom.

[0131] In this embodiment of the invention, by using a first aromatic hard segment having the above-described structure as the hard segment portion of the polyimide adhesive, the polyimide adhesive has better thermal stability and mechanical strength, thereby further improving the mechanical properties of the adhesive material while maintaining good bonding effect.

[0132] Furthermore, when the first aromatic hard segment is selected from the structures shown in Formulas I-1 to I-9, the thermal stability and mechanical strength of the polyimide binder can be further improved:

[0133]

[0134] R2 is selected from the structures shown in equation G and / or equation H as follows:

[0135]

[0136] The alkyl group is a straight-chain alkyl group or a branched alkyl group having 1 to 18 atoms. x1 represents the number of repeating units in formula G (x1 is generally a positive integer greater than 1), and x1 is an integer from 10 to 25. Preferably, R4 is selected from straight-chain alkyl groups or branched alkyl groups having 4 to 8 carbon atoms.

[0137]

[0138] R5 and R6 are each independently selected from straight-chain alkyl groups or branched alkyl groups, and y1 represents the repeating unit in formula H. The quantity (y1 is generally a positive integer greater than 1). R5 and R6 are each independently selected from straight-chain alkyl or branched alkyl with 1 to 12 carbon atoms, and y1 is an integer from 10 to 25. Preferably, R5 and R6 are each independently selected from straight-chain alkyl or branched alkyl with 1 to 3 carbon atoms.

[0139] In detail, the structure shown in Formula G is formed by the ring-opening polymerization of a lactone. During the ring-opening polymerization of the lactone, the carbon-oxygen single bond (CO) in the ester bond breaks, leading to the ring opening of the lactone. The broken ester bond then forms a linear polymer chain with another broken ester bond through chain polymerization, i.e., the repeating unit is formed by this chain. The polymer chain segments that make up the polymer chain.

[0140] R4 is selected from straight-chain alkyl groups or branched alkyl groups. Specifically, R4 is a straight-chain alkyl group or a branched alkyl group with a carbon number of C1 to C18 (e.g., an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18). Preferably, R4 is a straight-chain alkyl group or a branched alkyl group with a carbon number of C4 to C8 (e.g., an integer number of carbon atoms of 4, 5, 6, 7 or 8). For example, when R4 is a straight-chain alkyl group, it includes, but is not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.; when R4 is a branched alkyl group, it includes, but is not limited to, isopropyl, tert-butyl, isobutyl, sec-butyl, neopentyl, isopentyl, tert-pentyl, 3-methylbutyl, 2-methylbutyl, 2,2-dimethylpropyl, 2-methylpentyl, 3-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,2,3-trimethylbutyl, 2,2,4-trimethylpentyl, 2,4-dimethylpentyl, 3,3-dimethylbutyl, 3-methylhexyl, 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylhexyl, 2,2,5-trimethylhexyl, 2,2,4-trimethylpentyl, etc.

[0141] The structure shown in Formula H is formed by the ring-opening polymerization of lactones. In the ring-opening polymerization process of lactones in the embodiments of the present invention, the carbon-oxygen single bond (CO) in the ester bond breaks, resulting in the ring-opening of the lactone. The broken ester bond and another broken ester bond form a linear polymer chain through chain polymerization, that is, the repeating unit is formed by this repeating unit. The polymer chain segments that make up the polymer chain.

[0142] R5 is selected from straight-chain alkyl or branched alkyl. Specifically, R5 is a straight-chain alkyl or branched alkyl with a carbon number of C1 to C12 (such as an integer number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12). Preferably, R5 is a straight-chain alkyl or branched alkyl with a carbon number of C1 to C5 (such as an integer number of carbon atoms of 1, 2, 3, 4 or 5). For example, when R4 is a straight-chain alkyl group, it includes, but is not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.; when R4 is a branched alkyl group, it includes, but is not limited to, isopropyl, tert-butyl, isobutyl, sec-butyl, neopentyl, isopentyl, tert-pentyl, 3-methylbutyl, 2-methylbutyl, 2,2-dimethylpropyl, 2-methylpentyl, 3-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,2,3-trimethylbutyl, 2,2,4-trimethylpentyl, 2,4-dimethylpentyl, 3,3-dimethylbutyl, 3-methylhexyl, 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylhexyl, 2,2,5-trimethylhexyl, 2,2,4-trimethylpentyl, etc.

[0143] R6 is selected from straight-chain alkyl or branched alkyl. Specifically, R6 is a straight-chain alkyl or branched alkyl with a carbon number of C1 to C12 (e.g., an integer number of carbon atoms of 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12). Preferably, R5 is a straight-chain alkyl or branched alkyl with a carbon number of C1 to C5 (e.g., an integer number of carbon atoms of 1, 2, 3, 4 or 5). For example, when R6 is a straight-chain alkyl group, it includes, but is not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.; when R6 is a branched alkyl group, it includes, but is not limited to, isopropyl, tert-butyl, isobutyl, sec-butyl, neopentyl, isopentyl, tert-pentyl, 3-methylbutyl, 2-methylbutyl, 2,2-dimethylpropyl, 2-methylpentyl, 3-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,2,3-trimethylbutyl, 2,2,4-trimethylpentyl, 2,4-dimethylpentyl, 3,3-dimethylbutyl, 3-methylhexyl, 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylhexyl, 2,2,5-trimethylhexyl, 2,2,4-trimethylpentyl, etc.

[0144] R3 (i.e., the second aromatic hard segment) is selected from the structures shown in formulas XI-1 to XI-16 below:

[0145]

[0146] Furthermore, equation XI-1 can be a structure as shown in equation XI-11 below:

[0147]

[0148] Equation XI-2 can be a structure as shown in Equation XI-21 below:

[0149]

[0150] In order to better improve the problem of uneven molecular weight and distribution during the synthesis of polyester soft segments and maintain the stability of battery performance, in some embodiments of the present invention, an end-capping structure is introduced into the polyester soft segments. The end-capping structure includes the structure shown in Formula IV below:

[0151]

[0152] L1 is selected from aryl, straight-chain alkyl, or branched alkyl groups. The symbol * indicates the connection site between Formula IV and the ester group in the polyester soft segment, and the symbol * indicates the connection site between Formula IV and the aromatic hard segment. Specifically, it can be connected to a second aromatic hard segment, and the symbol * indicates the connection site between Formula IV and the aromatic hard segment.

[0153] When the structure shown in Formula IV is used as the end-capping structure in the embodiments of the present invention, it has good chemical stability, which is beneficial to improving the stability performance of polyimide adhesives.

[0154] L1 is selected from aryl, straight-chain alkyl, or branched alkyl. Specifically, L1 can be an aryl with C4 to C24 carbon atoms (e.g., an integer number of carbon atoms of 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, or 24), or a biaryl with 12 to 48 carbon atoms. L1 can also be a straight-chain alkyl or a branched alkyl with C1 to C12 carbon atoms (e.g., an integer number of carbon atoms of 5, 6, 7, 8, 9, 10, 11, or 12). Preferably, L1 can be an aryl with 6 carbon atoms. L1 can also be a straight-chain alkyl or a branched alkyl with C1 to C6 carbon atoms (e.g., an integer number of carbon atoms of 1, 2, 3, 4, 5, or 6). For example, when L1 is aryl, it includes, but is not limited to, phenyl, tolyl, xylyl, naphthyl, anthracene, phenanthryl, pyrene, biphenyl, terphenyl, tetrahydronaphthyl, indene, fluorenyl, acenaphthene, xanthyl, thiophene, furanyl, pyridyl, quinolinyl, isoquinolinyl, indolyl, carbazole, pyrrole, imidazolyl, thiazolyl, oxazolyl, benzothiophene, benzofuranyl, benzimidazolyl, benzothiazolyl, and benzoxazolyl, etc.; when L1 is a straight-chain alkyl group, it includes, but is not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, and n-dodecane. When L1 is a branched alkyl group, it includes, but is not limited to, isopropyl, tert-butyl, isobutyl, sec-butyl, neopentyl, isopentyl, tert-pentyl, 3-methylbutyl, 2-methylbutyl, 2,2-dimethylpropyl, 2-methylpentyl, 3-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,2,3-trimethylbutyl, 2,2,4-trimethylpentyl, 2,4-dimethylpentyl, 3,3-dimethylbutyl, 3-methylhexyl, 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylhexyl, 2,2,5-trimethylhexyl, 2,2,4-trimethylpentyl, etc. Preferably, the end-capping structure can be as follows:

[0155]

[0156] This invention, by introducing the aforementioned end-capping structure into the polyimide binder, achieves two advantages: firstly, a more uniform number-average molecular weight and molecular weight distribution in the polyimide binder; and secondly, a polymer system with both hard and soft segments, giving it good flexibility and suitable mechanical properties, which is beneficial for maintaining the integrity of the electrode active material layer during battery operation. During the polymerization reaction, the end-capping structure may connect to multiple sites in the polyester soft segments.

[0157] For example, the polyester soft segment can be selected from the following structures:

[0158]

[0159] Wherein, m and b are each independently the number of methylene groups in the polyester soft segment, and m and b are each independently an integer from 1 to 12, such as 1, 2, 3, 4, 5, 10, 12, etc.; a is the number of methylene groups on the side chains in the polyester soft segment, and a takes the value of an integer from 1 to 12, such as 1, 2, 3, 4, 5, 10, 12, etc.; x and y are each independently the number of repeating units in the polyester soft segment. m, a, b, x, and y can all be tested using conventional techniques in this field, such as nuclear magnetic resonance (NMR).

[0160] The embodiments of the present invention, by adding end-capping structures to the polyester soft segments, can effectively terminate the polymerization reaction, which is more conducive to controlling the molecular weight and distribution of the polymer, and makes the polyester soft segments have more stable properties.

[0161] In some embodiments, the mass percentage of polyester flexible segments in the polyimide binder is 10% to 90%. By controlling the mass percentage of polyester flexible segments in the polyimide binder within the range of 10% to 90%, the polyimide binder can possess both good flexibility and mechanical properties, as well as good adhesion properties, thereby improving the structural stability of the electrode sheet, avoiding problems such as electrode coating peeling, and ultimately improving the cycle life and other performance characteristics of the battery.

[0162] For example, the mass percentage of polyester soft segments in the polyimide adhesive can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%, etc.

[0163] In some embodiments, the polyester soft segment in the polyimide binder has a mass percentage of 30% to 60%, which helps to further balance the mechanical properties and flexibility of the polyimide binder, further improve the adhesion, flexibility and processability of the polyimide binder when used in electrode sheet preparation, improve the stability of the electrode slurry used to form the electrode sheet, the flexibility of the electrode sheet, the peel strength of the electrode sheet coating and current collector, and improve the cycle life of the battery.

[0164] According to the inventors' research, by introducing a first aromatic hard segment, a polyester soft segment, and a second aromatic hard segment structure into the polyimide binder, the anti-swelling performance of the polyimide binder is improved. This effectively prevents the polyimide binder from expanding and softening due to excessive solvent absorption, thus preventing the electrode sheet from shedding material during battery operation. Simultaneously, it improves the adhesion, flexibility, and processability of the binder material during electrode sheet preparation, enhancing the bonding strength between the electrode coating and the electrode current collector, and preventing problems such as electrode sheet peeling (e.g., electrode coating peeling from the electrode current collector, electrode coating cracking, and powder shedding). This improves the stability and flexibility of the electrode sheet, thereby increasing the battery's cycle life.

[0165] Introducing a second aromatic hard segment into the polyimide composition system of this invention can further enhance the mechanical properties of the polyimide binder on the basis of improving adhesion, mechanical properties, and flexibility, so that the electrode maintains integrity and stability during battery operation and avoids material shedding and peeling.

[0166] In some embodiments, the number average molecular weight of the polyimide binder is between 10 kDa and 10,000 kDa. For example, the number average molecular weight of the polyimide binder is, for example, a range of 10 kDa, 100 kDa, 500 kDa, 1000 kDa, 5000 kDa, 10000 kDa, or any combination thereof. When the number average molecular weight of the polyimide binder is within the above range, it can be ensured that the polyimide binder has good solubility and processability while providing sufficient mechanical strength and heat resistance for the battery electrodes, thereby improving the cycle stability and lifespan of the battery.

[0167] In this embodiment of the invention, the number-average molecular weight of the polyimide binder can be determined by gel permeation chromatography (GPC). The prepared polyimide binder is dissolved in N-methylpyrrolidone to prepare a 2 mg / mL sample solution. The sample solution is injected into a gel permeation chromatograph (Agilent PL-GPC 220, test temperature 50°C) with N-methylpyrrolidone as the mobile phase. The obtained curve is calibrated with polystyrene of known molecular weight to obtain the number-average molecular weight of the polyimide binder.

[0168] The polyimide binder enhances the chemical stability of the electrolyte, preventing adverse chemical reactions between residual ester monomers and the electrolyte or electrode materials, protecting the active materials of the battery, and thus improving the battery's cycle performance.

[0169] On the other hand, embodiments of the present invention provide an electrode sheet including an electrode coating, the electrode coating comprising the above-described polyimide binder, or a polyimide binder prepared according to the above-described method for preparing the binder material. This electrode sheet has advantages corresponding to the above-described polyimide binder, which will not be elaborated further.

[0170] The electrode sheet provided in this embodiment of the invention is prepared by using the above-mentioned polyimide binder, which can reduce the occurrence of peeling, cracking and powdering of the electrode active material layer in the electrode sheet, so that the electrode sheet can maintain its integrity structure even when the battery is working for a long time, which greatly improves the safety, cycle stability and service life of the battery.

[0171] In this embodiment of the invention, the polyimide binder can be used only in the positive electrode of the battery, only in the negative electrode of the battery, or in both the positive and negative electrodes of the battery. In specific implementation, the polyimide binder can be used in the positive electrode of the battery, and the polyimide binder can better adapt to the volume changes of the positive electrode of the battery during charge and discharge cycles.

[0172] It should be clarified that the aforementioned polyimide binder can be used alone in the battery electrode sheet, or it can be used in combination with other binders conventionally used in the art in the battery electrode sheet.

[0173] The electrode sheet includes an electrode current collector and an electrode active material layer located on at least one side of the electrode current collector. Specifically, the electrode active material layer may be located on only one side of the electrode current collector, or the electrode active material layer may be provided on both sides of the electrode current collector.

[0174] Furthermore, the embodiments of the present invention do not impose special limitations on the single-sided density of the electrode sheet; for example, the areal density of the electrode sheet can be 50–700 g / m². 2 In practical implementation, the density of one side of the electrode sheet can be 200 g / m². 2 .

[0175] In this embodiment of the invention, the test process for the single-sided density of the electrode coating is as follows: Take an electrode sheet (positive electrode sheet or negative electrode sheet) sample (specifically, a cutter can be used to cut the negative electrode sheet to obtain a negative electrode sheet sample of suitable size), test the total mass m1 of the electrode sheet sample, the total thickness T1 of the electrode sheet sample (T1 = total thickness of the electrode active material layer + thickness of the electrode current collector; when the electrode current collector has electrode active material layers on both the positive and negative surfaces, the total thickness of the electrode active material layer = thickness of the electrode active material layer on one side of the electrode current collector + thickness of the electrode active material layer on the other side of the electrode current collector), and the surface area S of one side of the electrode sheet sample in the thickness direction; then scrape off the electrode active material layer on the electrode sheet sample, test the mass m2 of the obtained electrode current collector, and the thickness T2 of the electrode current collector, then the total thickness of the electrode active material layer = T1 - T2, and the surface density of the electrode active material layer = (m1 - m2) / S.

[0176] In detail, when the electrode sheet is a positive electrode sheet, the electrode current collector is a positive electrode current collector, and the electrode active material layer is a positive electrode active material layer. Specifically, the positive electrode active layer can be provided on one side of the surface in the thickness direction of the positive electrode current collector, or the positive electrode active layer can be provided on both sides of the opposite surface in the thickness direction of the positive electrode current collector.

[0177] The positive electrode active material layer may include positive electrode active material, conductive agent and binder. In the positive electrode coating, the mass percentage of positive electrode active material may be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99% or any combination thereof. The mass fraction of binder may be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or any combination thereof.

[0178] The binder for the positive electrode active material layer can be the binder material provided in the embodiments of the present invention, or it can be a composite of one or more of the following: polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, etc., used as the binder for the positive electrode active material layer.

[0179] In some embodiments, the positive electrode active material may include LiCoO2, LiNiO2, or LiCo. x Ni 1-x O2 (0≤x≤1), LiCo x Ni 1-x-y Al yO2(0≤x≤1,0≤y≤1), LiMn2O4, LiFe x Mn y M z O4 (M is one or more of Al, Mg, Ga, Cr, Co, Ni, Cu, Zn or Mo, 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1), Li 1+x L 1-y-z M y N z O2 (L, M, N are one or more of Li, Co, Mn, Ni, Fe, Al, Mg, Ga, Ti, Cr, Cu, Zn, Mo, F, I, S, B, -0.1≤x≤0.2, 0≤y≤1, 0≤z≤1, 0≤y+z≤1), LiFePO4, Li3V2(PO4)3, Li3V3(PO4)3, LiVPO4F, Li2CuO2, Li5FeO4, and metal sulfides and oxides (such as TiS2, V2S3, FeS, FeS2, LiMS) x (M is at least one of the transition metal elements such as Ti, Fe, Ni, Cu, Mo, etc., 1≤x≤2.5), TiO2, Cr3O8, V2O5, MnO2, etc.

[0180] The embodiments of the present invention may employ conventional positive current collectors in the art, for example, positive current collectors may include aluminum foil.

[0181] In this embodiment of the invention, the positive electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the positive electrode active material, conductive agent, binder, and other components used to form the positive electrode active layer can be dispersed in a solvent, such as N-methylpyrrolidone (NMP), to prepare a positive electrode slurry. This slurry is then coated onto the surface of the positive electrode current collector, and after drying, rolling, and other processes, the positive electrode sheet is obtained. The coating, drying, and rolling processes involved are conventional operations for preparing positive electrode sheets using the coating method, and are not particularly limited thereto.

[0182] In one specific embodiment, when the electrode sheet is a negative electrode sheet, the electrode current collector is a negative electrode current collector. A negative electrode active material layer can be provided on one side surface of the negative electrode current collector in the thickness direction, or negative electrode active material layers can be provided on both opposite sides surface in the thickness direction of the negative electrode current collector.

[0183] In this embodiment of the invention, the binder in the negative electrode active material layer can be either the binder material provided in this embodiment of the invention or a binder that is suitable for any negative electrode and is known in the art. For example, at least one of the following can be used together with the binder material provided in this embodiment of the invention to prepare the negative electrode active material layer: polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), tetrafluoroethylene and its copolymers, polyvinylidene fluoride and its copolymers, polyolefins and their copolymers (e.g., polyethylene-polyethylene glycol block copolymers), polyethers and their copolymers (e.g., polyethylene oxide), polyphenylene ethers and their copolymers, polysiloxanes and their copolymers (e.g., polydimethylsiloxane, poly(dimethylsiloxane-co-alkylmethylsiloxane)), polyesters and their copolymers (e.g., polyethylene ester, polyvinyl acetate, polyacrylate), carboxymethyl cellulose, styrene-butadiene latex, nitrile rubber, and polyacrylic acid (PAA).

[0184] Specifically, polyolefins include one or more of polyethylene, polypropylene, ethylene / propylene copolymer, ethylene / vinylidene fluoride copolymer, and propylene / vinylidene fluoride copolymer; polytetrafluoroethylene and its copolymers may be at least one of tetrafluoroethylene / ethylene copolymer, tetrafluoroethylene / propylene copolymer, tetrafluoroethylene / vinylidene fluoride copolymer, tetrafluoroethylene / ether copolymer, tetrafluoroethylene / branched polyether copolymer, tetrafluoroethylene / vinyl ether copolymer, tetrafluoroethylene / branched polyether / vinyl ether copolymer, and tetrafluoroethylene / siloxane copolymer.

[0185] In addition, the negative electrode active material layer also includes a negative electrode active material. Specifically, the negative electrode active material may include graphite, and the conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fiber. Generally, the mass percentage of the negative electrode active material in the negative electrode active material layer can be 80% to 100%, and the mass percentage of the negative electrode active material in the negative electrode active material layer can be, for example, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 100%, or any combination thereof.

[0186] The embodiments of the present invention may employ conventional negative electrode current collectors in the art, for example, negative electrode current collectors include copper foil.

[0187] In embodiments of the present invention, the negative electrode sheet can be prepared by a dry process (i.e., rolling the material used to form the negative electrode active layer into a film and then combining it with the negative electrode current collector to obtain the negative electrode sheet), or by a wet process (coating method) (i.e., coating the negative electrode slurry used to form the negative electrode active layer onto the surface of the negative electrode current collector, and then drying, rolling and other processes to form the negative electrode active layer on the surface of the negative electrode sheet to obtain the negative electrode sheet).

[0188] On the other hand, embodiments of the present invention provide a battery including the electrode sheets described above. This battery has advantages corresponding to the polyimide binder described above, which will not be elaborated further.

[0189] Generally, a battery includes an electrolyte, a battery cell, and a casing for encapsulating the battery cell. The electrolyte is injected into the battery cell within the casing. The battery cell includes electrode plates (including positive and negative electrode plates) and a separator located between the positive and negative electrode plates. The battery cell can be a stacked cell, meaning it is composed of positive electrode plates, a separator, and negative electrode plates stacked alternately; or it can be a wound cell, meaning it is composed of positive electrode plates, a separator, and negative electrode plates stacked and then wound together. In practice, a stacked cell can be formed by alternating layers of positive electrode plates, a separator, and negative electrode plates, and then the cell is encapsulated using an aluminum-plastic film.

[0190] The electrolyte in this embodiment of the invention can be a conventional electrolyte in the art. For example, the electrolyte is a non-aqueous electrolyte, which may specifically include organic solvents, additives and electrolyte salts. Organic solvents include one or more of ethylene carbonate (EC), diethyl carbonate (DEC) and propylene carbonate (PC). Additives include, for example, fluoroethylene carbonate (FEC) and vinylene carbonate (VC). Electrolyte salts may include lithium salts, such as lithium hexafluorophosphate (LiPF6), but are not limited thereto.

[0191] In this embodiment of the invention, the separator is used to separate the positive electrode and the negative electrode to prevent the positive electrode and the negative electrode from short-circuiting due to contact. Conventional separators in the art can be used in this embodiment of the invention, and there are no special limitations on this.

[0192] In this embodiment of the invention, the battery cell can be packaged using conventional housing materials in the art, such as flexible packaging materials like aluminum-plastic film, but is not limited thereto.

[0193] The embodiments of the present invention can assemble components such as positive electrode, separator and negative electrode into a battery using conventional methods in the art. For example, positive electrode, separator and negative electrode can be stacked in an alternating manner to obtain a stacked cell (or wound into a wound cell); then the cell is placed in a casing (outer packaging) and after conventional processes such as electrolyte injection, encapsulation, formation and capacity testing, a battery is obtained.

[0194] Furthermore, the present invention does not specifically limit the type of battery. In some embodiments, the battery can be a lithium-ion battery or a sodium-ion battery.

[0195] When the battery is a sodium-ion battery, the positive electrode active material includes, but is not limited to, one or a combination of transition metal oxides, polyanionic compounds, organic polymers, and Prussian blue materials.

[0196] The present invention also provides a battery pack comprising at least two of the above-described batteries connected to each other, which has advantages corresponding to the above-described polyimide binder, which will not be elaborated further.

[0197] Generally, a battery pack includes multiple batteries as individual cells, which are connected to form the battery pack. These batteries can be electrically connected using methods conventional in the art, such as series connection, parallel connection, or a combination of these connection methods, without any particular limitation.

[0198] The present invention also provides an electrical device comprising the aforementioned battery or battery pack. This electrical device has advantages corresponding to the aforementioned polyimide adhesive, which will not be elaborated further.

[0199] The electrical equipment provided by this invention can be conventional electrical equipment in the field, such as power equipment (e.g., electric vehicles, electric cars), electrical equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., without any particular limitation.

[0200] The technical solution of the present invention will be further described below with reference to specific embodiments.

[0201] Example 1

[0202] The preparation process of the polyimide adhesive in this embodiment is as follows:

[0203] 1) Add 62g of ethylene glycol and 1.14kg of caprolactone to 1000mL of N-methylpyrrolidone (NMP), mix well, and carry out the first reaction at 150℃ for 5h to obtain a hydroxyl-terminated polyester precursor.

[0204] The molar ratio of ethylene glycol to caprolactone is 1:10;

[0205] 2) The hydroxyl-terminated polyester precursor was then mixed with 160g of p-phenyl diisocyanate and subjected to a second reaction at 80°C for 10h to obtain an intermediate product (including isocyanate-terminated polyester precursor and diisocyanate).

[0206] The molar ratio of p-phenyl diisocyanate to caprolactone is 0.1:1;

[0207] 3) Add 914.64g of terephthalic anhydride monomer to the intermediate product obtained in step 2), and carry out the third reaction at 50°C for 10h. At the same time, carbon dioxide is removed from the system to obtain polyimide solution.

[0208] The molar ratio of terephthalic anhydride monomer to caprolactone is 0.618:1;

[0209] 4) The polyimide solution obtained in step 3) is placed in ethanol for precipitation and separation to obtain a solid product and a supernatant. The solid product is dried to obtain the polyimide adhesive.

[0210] The volume ratio of ethanol to polyimide solution is 4:1, and the precipitation time is 1 hour, which can better remove residual ester monomers from the polyimide solution.

[0211] The preparation process of the positive electrode sheet in this embodiment is as follows:

[0212] 1) Mix lithium iron phosphate, carbon black, the above-mentioned polyimide binder, and NMP in a mass ratio of 100:2.0:1.0:52 and stir for 1 hour to obtain the positive electrode slurry.

[0213] 2) The above-mentioned positive electrode slurry is coated onto the surface of aluminum foil, and then dried, rolled, and slit to obtain a positive electrode sheet. Both sides of the positive electrode sheet are provided with a positive electrode active material layer; the surface density of the positive electrode active material layer on one side is 200 g / m³. 2 .

[0214] The battery manufacturing process in this embodiment is as follows:

[0215] The above-mentioned positive electrode sheet, polypropylene separator, and graphite negative electrode sheet are stacked, packaged in an aluminum-plastic film, and then injected with electrolyte (1MLiPF6-EC / DMC (1:1 vol%)). After sealing and formation, they are ready for use.

[0216] Example 2

[0217] This embodiment is basically the same as Embodiment 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 180°C for 5 hours.

[0218] Example 3

[0219] This embodiment is basically the same as Embodiment 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 150°C for 7 hours.

[0220] Example 4

[0221] This embodiment is basically the same as Embodiment 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 180°C for 7 hours.

[0222] Example 5

[0223] This embodiment is basically the same as Embodiment 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 150°C for 10 hours.

[0224] Example 6

[0225] This embodiment is basically the same as Embodiment 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 180°C for 10 hours.

[0226] Example 7

[0227] This embodiment is basically the same as Embodiment 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 200°C for 15 hours.

[0228] Example 8

[0229] This embodiment is basically the same as Embodiment 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 120°C for 5 hours.

[0230] Example 9

[0231] This embodiment is basically the same as Embodiment 1, except that the preparation process of the polyimide adhesive is as follows:

[0232] 1) Add 60g of ethylenediamine and 1.16kg of glycolide to 1000mL of N-methylpyrrolidone (NMP) solvent, mix well, and carry out the first reaction at 130℃ for 8h to obtain a hydroxyl-terminated polyester precursor.

[0233] The molar ratio of ethylenediamine to glycolide is 1:10;

[0234] 2) The hydroxyl-terminated polyester precursor was then mixed with 264g of diisocyanate and subjected to a second reaction at 80°C for 10h to obtain an intermediate product (including isocyanate-terminated polyester precursor and diisocyanate).

[0235] The molar ratio of diisocyanate to glycolide is 0.1:1;

[0236] 3) Add 1841.64g of dianhydride monomer to the intermediate product obtained in step 2), and carry out the third reaction at 50°C for 10h. At the same time, carbon dioxide is removed from the system to obtain polyimide solution.

[0237] The molar ratio of dianhydride monomer to glycolide is 0.618:1;

[0238] 4) The polyimide solution obtained in step 3) is placed in ethanol for precipitation and separation to obtain a solid product and a supernatant. The solid product is dried to obtain the polyimide adhesive.

[0239] A volume ratio of ethanol to polyimide solution of 4:1 and a precipitation time of 1 hour can better remove residual ester monomers from the polyimide solution.

[0240] Among them, diisocyanate is Dicarboxylic anhydride monomer is

[0241]

[0242] Example 10

[0243] This embodiment is basically the same as Embodiment 1, except that the preparation process of the polyimide adhesive is as follows:

[0244] 1) Add 62g of ethylene glycol and 0.57kg of caprolactone to 1000mL of N-methylpyrrolidone (NMP), mix well, and carry out the first reaction at 165℃ for 7h to obtain a hydroxyl-terminated polyester precursor.

[0245] The molar ratio of ethylene glycol to caprolactone is 1:5;

[0246] 2) The hydroxyl-terminated polyester precursor was then mixed with 160g of p-phenyl diisocyanate and subjected to a second reaction at 70°C for 6 hours to obtain an intermediate product (including isocyanate-terminated polyester precursor and diisocyanate).

[0247] The molar ratio of p-phenyl diisocyanate to caprolactone is 0.1:1;

[0248] 3) Add 103.6g of terephthalic anhydride monomer to the intermediate product obtained in step 2), and carry out the third reaction at 40°C for 6 hours. At the same time, carbon dioxide is removed from the system to obtain polyimide solution.

[0249] The molar ratio of terephthalic anhydride monomer to caprolactone is 0.07:1;

[0250] 4) The polyimide solution obtained in step 3) is placed in ethanol for precipitation and separation to obtain a solid product and a supernatant. The solid product is dried to obtain the polyimide adhesive.

[0251] The volume ratio of ethanol to polyimide solution is 4:1, and the precipitation time is 1 hour, which can better remove residual ester monomers from the polyimide solution.

[0252] Example 11

[0253] This embodiment is basically the same as Example 1, except that in the preparation process of the polyimide adhesive, in step 1), 6.2g of ethylene glycol and 1.14kg of caprolactone are added to 1000mL of N-methylpyrrolidone (NMP), mixed evenly, and the first reaction is carried out at 150℃ for 5h to obtain a hydroxyl-terminated polyester precursor; the molar ratio of ethylene glycol to caprolactone is 1:100; 3) 1953.6g of terephthalic anhydride monomer is added to the intermediate product obtained in step 2), and the third reaction is carried out at 50℃ for 10h, while carbon dioxide is removed from the system to obtain a polyimide adhesive; the molar ratio of terephthalic anhydride monomer to caprolactone is 1.32:1.

[0254] Example 12

[0255] This embodiment is basically the same as Example 1, except that in the preparation process of the polyimide adhesive, in step 1), 20.67g of ethylene glycol and 1.14kg of caprolactone are added to 1000mL of N-methylpyrrolidone (NMP), mixed evenly, and the first reaction is carried out at 150℃ for 5h to obtain the hydroxyl-terminated polyester precursor; the molar ratio of ethylene glycol to caprolactone is 1:30.

[0256] Example 13

[0257] This embodiment is basically the same as Example 1, except that in step 2) of the preparation process of polyimide adhesive, the hydroxyl-terminated polyester precursor obtained in step 1) is mixed with 4.8 kg of p-phenyl diisocyanate and the second reaction is carried out at 80°C for 10 h to obtain an intermediate product (including isocyanate-terminated polyester precursor and diisocyanate).

[0258] The molar ratio of p-phenyl diisocyanate to caprolactone is 3:1.

[0259] Example 14

[0260] This embodiment is basically the same as that of Embodiment 1, except that in step 2) of the preparation process of polyimide adhesive, the hydroxyl-terminated polyester precursor obtained in step 1) is mixed with 32 kg of p-phenyl diisocyanate and subjected to a second reaction at 80°C for 10 h to obtain an intermediate product (including isocyanate-terminated polyester precursor and diisocyanate).

[0261] The molar ratio of p-phenyl diisocyanate to caprolactone is 20:1.

[0262] Example 15

[0263] This embodiment is basically the same as that of embodiment 1, except that in step 2) of the preparation process of polyimide adhesive, the hydroxyl-terminated polyester precursor obtained in step 1) is mixed with 80 kg of p-phenyl diisocyanate and the second reaction is carried out at 80°C for 10 h to obtain an intermediate product (including isocyanate-terminated polyester precursor).

[0264] The molar ratio of p-phenyl diisocyanate to caprolactone is 50:1.

[0265] Example 16

[0266] This embodiment is basically the same as that of Example 1, except that in step 2) of the preparation process of polyimide adhesive, the hydroxyl-terminated polyester precursor obtained in step 1) is mixed with 112 kg of p-phenyl diisocyanate and the second reaction is carried out at 80°C for 10 h to obtain an intermediate product (including isocyanate-terminated polyester precursor).

[0267] The molar ratio of p-phenyl diisocyanate to caprolactone is 70:1.

[0268] Example 17

[0269] This embodiment is basically the same as Embodiment 1, except that in step 2) of the preparation process of the polyimide adhesive, the second reaction is carried out at 90°C for 15 hours; and in step 3) the third reaction is carried out at 60°C for 15 hours.

[0270] Example 18

[0271] This embodiment is basically the same as Embodiment 1, except that in step 2) of the preparation process of the polyimide adhesive, the second reaction is carried out at 80°C for 1 hour; and in step 3) the third reaction is carried out at 50°C for 1 hour.

[0272] Example 19

[0273] This embodiment is basically the same as Embodiment 1, except that in step 2) of the preparation process of the polyimide adhesive, the second reaction is carried out at 60°C for 0.5 hours.

[0274] Example 20

[0275] This embodiment is basically the same as that of Embodiment 1, except that in step 2) of the preparation process of the polyimide adhesive, the second reaction is carried out at 110°C for 17 hours.

[0276] Example 21

[0277] This embodiment is basically the same as that of Embodiment 1, except that in step 3) of the preparation process of the polyimide adhesive, the third reaction is carried out at 30°C for 0.5 hours.

[0278] Example 22

[0279] This embodiment is basically the same as that of Embodiment 1, except that in step 3) of the preparation process of the polyimide adhesive, the third reaction is carried out at 80°C for 17 hours.

[0280] Example 23

[0281] This embodiment is basically the same as Example 1, except that in the preparation process of the polyimide adhesive, in step 1), 206.7g of ethylene glycol and 1.14kg of caprolactone are added to 1000mL of N-methylpyrrolidone (NMP), mixed evenly, and the first reaction is carried out at 150℃ for 5h to obtain the hydroxyl-terminated polyester precursor; the molar ratio of ethylene glycol to caprolactone is 1:3.

[0282] Example 24

[0283] This embodiment is basically the same as Example 1, except that in the preparation process of the polyimide adhesive, in step 1), 5.64g of ethylene glycol and 1.14kg of caprolactone are added to 1000mL of N-methylpyrrolidone (NMP), mixed evenly, and the first reaction is carried out at 150℃ for 5h to obtain the hydroxyl-terminated polyester precursor; the molar ratio of ethylene glycol to caprolactone is 1:110.

[0284] Example 25

[0285] This embodiment is basically the same as Example 1, except that in the preparation process of the polyimide adhesive, in step 3), 74g of terephthalic anhydride monomer is added to the intermediate product obtained in step 2), and a third reaction is carried out at 50°C for 10h. At the same time, carbon dioxide is removed from the system to obtain polyimide adhesive; the molar ratio of terephthalic anhydride monomer to caprolactone is 0.05:1.

[0286] Example 26

[0287] This embodiment is basically the same as Example 1, except that in the preparation process of the polyimide adhesive, in step 3), 2220g of terephthalic anhydride monomer is added to the intermediate product obtained in step 2), and a third reaction is carried out at 50°C for 10h. At the same time, carbon dioxide is removed from the system to obtain polyimide adhesive; the molar ratio of terephthalic anhydride monomer to caprolactone is 1.5:1.

[0288] Comparative Example 1

[0289] This comparative example is basically the same as Example 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 60°C for 3 hours.

[0290] Comparative Example 2

[0291] This comparative example is basically the same as Example 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 90°C for 3 hours.

[0292] Comparative Example 3

[0293] This comparative example is basically the same as Example 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 120°C for 3 hours.

[0294] Comparative Example 4

[0295] This comparative example is basically the same as Example 1, except that in step 1) of the preparation process of the polyimide adhesive, the first reaction is carried out at 150°C for 3 hours.

[0296] The temperatures and times of the first, second, and third reactions, as well as the molar ratios of the initiator to the ester monomer (M1), diisocyanate to the ester monomer (M2), dianhydride monomer to the ester monomer (M3), the types of antisolvents, initiators, ester monomers, diisocyanates, and dianhydride monomers in each embodiment and comparative example, are summarized in Tables 1 and 2. Except for the differences shown in Tables 1 and 2, the other conditions are basically the same.

[0297] Table 1

[0298]

[0299]

[0300] Table 2

[0301]

[0302]

[0303] The conversion rates of the ester monomers in Examples 1-26 and Comparative Examples 1-4 were determined by gas chromatography (GC), and the specific steps are as follows:

[0304] 1) Preparation of internal standard solution: Weigh 10 mg of n-dodecane (purity ≥99%) (n-dodecane is the internal standard), dilute to 10 mL with methanol to prepare a 1 mg / mL internal standard stock solution, store at 4℃, take 1 mL of the stock solution and dilute to 10 mL with methanol to obtain a 100 μg / mL internal standard solution.

[0305] 2) Sample preparation: The polyimide adhesive prepared in step 3) of the preparation process of polyimide adhesives in Examples 1-26 and Comparative Examples 1-4 was dried to remove the solvent and obtain solid powder. 0.1g of the above solid powder (hereinafter referred to as sample) was weighed and 10mL of methanol (containing 0.1% formic acid, used to stabilize isocyanate) was added; 100μL of the internal standard solution prepared in step 1) was added to make the sample concentration in n-dodecane 1μg / mL, and the mixture was vortexed for 5 minutes; then ultrasonically treated for 30min (40℃) to accelerate the dissolution and release of residual ester monomers; the mixture was filtered through a 0.22μm PTFE filter membrane, the first 1mL of filtrate was discarded, and the subsequent filtrate was collected as sample stock solution;

[0306] 3) Preparation of Standards (including internal standard): 3-1) Using NMP, p-phenyl diisocyanate, or terephthalic anhydride as the standard solute and methanol as the solvent, prepare standard solutions with a solute concentration of 1 mg / mL; 3-2) Standard curve (gradient concentration): The standard gradient includes different concentrations of 0.1 μg / mL, 0.5 μg / mL, 1 μg / mL, 5 μg / mL, and 10 μg / mL; Internal standard addition: Add an equal amount of internal standard (n-dodecane, with a final internal standard concentration of 1 μg / mL) to each concentration level of standard.

[0307] 4) Preparation of the sample solution: Example preparation steps (taking 1 μg / mL as an example): Take 1 mL of sample stock solution and dilute it with methanol to 100 mL to obtain a 10 μg / mL intermediate solution. Take 10 μL of the intermediate solution, 90 μL of methanol, and 100 μL of internal standard solution and mix them together to make a total volume of 1 mL (wherein, the sample concentration is 1 μg / mL and the internal standard concentration is 1 μg / mL).

[0308] 5) GC Testing: Column: DB-5MS (30m × 0.25mm × 0.25μm) column, suitable for analysis with a wide polarity range. Temperature Program Settings: Injector: Temperature 250℃, split ratio 10:1; Detector (FID): Temperature 300℃, hydrogen flow rate 40mL / min, air flow rate 400mL / min; Oven: Initial temperature 50℃ (hold for 2 min), ramp to 200℃ at a rate of 10℃ / min, then ramp to 280℃ at a rate of 5℃ / min (hold for 5 min). Carrier Gas: Helium is used as the carrier gas, with a flow rate set to 1.0mL / min and kept constant. Injection Volume: 1μL is injected using an autosampler.

[0309] 6) Data Analysis: Data analysis was performed using the internal standard method. 5-1) Peak Area Ratio Calculation: For each standard and sample, the ratio (R) of the sample peak area to the internal standard peak area was calculated; 5-2) Standard Curve Fitting: A linear equation was fitted with the concentration (X) of the standard as the abscissa and the R value as the ordinate; 5-3) Sample Concentration Calculation: The sample concentration was calculated by substituting the R value of the sample into the fitted linear equation.

[0310] 7) Calculation of ester monomer conversion rate: Ester monomer conversion rate = (total mass of ester monomer - residual mass of ester monomer) / total mass of ester monomer, where the residual mass of ester monomer is calculated from the sample concentration measured by GC. The ester monomer conversion rate results are shown in Table 3.

[0311] The batteries assembled in Examples 1-26 and Comparative Examples 1-4 were subjected to constant current charge and discharge at room temperature within a voltage window of 2.0 to 3.8V at a charge / discharge rate of 1C / 1C: (1) After 200 cycles, the ratio of the battery discharge capacity after 200 cycles to the initial capacity is the battery's capacity retention rate after 200 cycles; (2) After 500 cycles, the ratio of the battery discharge capacity after 500 cycles to the initial capacity is the battery's capacity retention rate after 500 cycles; (3) After 1000 cycles, the ratio of the battery discharge capacity after 1000 cycles to the initial capacity is the battery's capacity retention rate after 1000 cycles. The test results are shown in Table 3.

[0312] Table 3

[0313]

[0314]

[0315] Analysis of Table 3 shows that in Comparative Examples 1 and 2, during the preparation of the polyimide binder, the temperature of the first reaction was less than 120℃ and the reaction time was less than 5 hours, resulting in a significant decrease in the conversion rate of the ester monomer and a severe deterioration in the battery's cycle performance. In Comparative Examples 3 and 4, during the preparation of the polyimide binder, the temperature of the first reaction was ≥120℃, but the reaction time was less than 5 hours, yet the conversion rate of the ester monomer still decreased significantly, and the battery's cycle performance deteriorated severely.

[0316] Compared to Comparative Examples 1 to 4, Examples 1 to 26 improved the conversion rate of ester monomers and the cycle performance of batteries by controlling the temperature of the first reaction to be ≥120°C and the time of the first reaction to be ≥5h.

[0317] Further, as can be seen from Examples 1 and 7-8, compared with Examples 7-8, Example 1, by further controlling the temperature of the first reaction to be in the range of 150-180°C and the time of the first reaction to be in the range of 5-10h, is conducive to further improving the conversion rate of ester monomers and the cycle performance of the battery.

[0318] Furthermore, a comparison between Example 1 and Examples 19-20 shows that, compared to Examples 19-20, Example 1, by controlling the temperature of the second reaction to be between 70 and 90°C and the time of the second reaction to be between 1 and 15 hours, is beneficial to further improve the cycle performance of the battery.

[0319] Furthermore, as can be seen from Examples 1 and 21-22, compared with Examples 21-22, Example 1, by controlling the temperature of the third reaction to be in the range of 40-60°C and the time of the third reaction to be in the range of 1-15h, is conducive to further improving the cycle performance of the battery.

[0320] Furthermore, as can be seen from Examples 1 and 23-24, compared with Examples 23-24, Example 1, by controlling the molar ratio of initiator to ester monomer within the range of 1:(5-100), is beneficial to further improve the cycle performance of the battery.

[0321] Furthermore, as can be seen from Examples 1 and 25-26, compared with Examples 25-26, Example 1, by controlling the molar ratio of dianhydride monomer to ester monomer within the range of (0.07-1.32):1, is beneficial to further improve the cycle performance of the battery.

[0322] Further, as can be seen from Examples 1 and 13 to 15, compared with Example 1, Examples 13 to 15 further improve the cycle performance of the battery by controlling the molar ratio of diisocyanate to ester monomer in the range of 1:(3 to 50).

[0323] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a polyimide adhesive, characterized in that, Includes the following steps: (1) The ester monomer is subjected to a first reaction under the action of an initiator to obtain a hydroxyl-terminated polyester precursor; (2) The hydroxyl-terminated polyester precursor and diisocyanate are mixed and a second reaction is carried out to obtain an intermediate product. (3) Add the dianhydride monomer to the intermediate product to carry out the third reaction to obtain the polyimide binder; In the first reaction, the reaction temperature is ≥120℃ and the reaction time is ≥5h.

2. The preparation method according to claim 1, characterized in that, In the first reaction, the reaction temperature is 120–180℃ and the reaction time is 5–10 h.

3. The preparation method according to claim 1 or 2, characterized in that, In the second reaction, the reaction temperature is 70–90°C and the reaction time is 1–15 h.

4. The preparation method according to any one of claims 1-3, characterized in that, In the third reaction, the reaction temperature is 40–60°C and the reaction time is 1–15 h.

5. The preparation method according to any one of claims 1-4, characterized in that, The molar ratio of the initiator to the ester monomer is 1:(5-100).

6. The preparation method according to any one of claims 1-5, characterized in that, The molar ratio of the diisocyanate to the ester monomer is (0.1-50):

1.

7. The preparation method according to any one of claims 1-6, characterized in that, The molar ratio of the dianhydride monomer to the ester monomer is (0.07-1.32):

1.

8. The preparation method according to any one of claims 1-7, characterized in that, The ester monomers include cyclic ester monomers, preferably lactones and / or lactones.

9. The preparation method according to any one of claims 1-8, characterized in that, The initiator includes a small molecule diol initiator and / or a small molecule diamine initiator.

10. The preparation method according to claim 8, characterized in that, The lactone has the structure shown in Formula A: R7 is a straight-chain alkyl group or a branched alkyl group having 1 to 12 carbon atoms. The lactone has the structure shown in Formula B: R8 and R9 are each independently selected from straight-chain alkyl groups having 1 to 12 carbon atoms or branched alkyl groups.

11. The preparation method according to claim 8, characterized in that, The lactone has the structure shown in formula C: Where a1, b1, and c1 are the number of methylene groups at the corresponding positions of the monomer, a1 is an integer from 0 to 11, b1 is an integer from 0 to 12, and c1 is an integer from 0 to 12. The lactone has the structure shown in formula D: Where a2 and b2 are the number of methylene groups at the corresponding positions of the monomer, with a2 being an integer from 1 to 10; and b2 being an integer from 1 to 10.

12. The preparation method according to any one of claims 1-11, characterized in that, The diisocyanate is selected from the structures shown in formulas XII-1 to XII-16 below:

13. The preparation method according to any one of claims 1-12, characterized in that, The dianhydride monomer is selected from the structures shown in formulas X-1 to X-9 below:

14. The preparation method according to any one of claims 1-13, characterized in that, The process of adding dianhydride monomer to the intermediate product and carrying out a third reaction to obtain polyimide adhesive includes: adding dianhydride monomer to the intermediate product and carrying out a third reaction to obtain polyimide solution; placing the polyimide solution in an antisolvent for precipitation and separation to obtain a solid product, which is the polyimide adhesive. The antisolvent includes one or more of ethanol, propanol, and isopropanol.

15. A polyimide adhesive, characterized in that, The polyimide adhesive is prepared by the preparation method according to any one of claims 1-14.

16. The polyimide adhesive according to claim 15, characterized in that, The polyimide adhesive has a structure as shown in formula E1 or formula E2: Where x is an integer from 5 to 500, and y is an integer from 0 to 500; R1 is selected from substituted or unsubstituted aryl groups, or substituted or unsubstituted biaryl groups; Preferably, the substituted or unsubstituted biaryl group has the structure shown in formula F: R 10 and R 11 Each independently represents a monosubstituted to the maximum permissible substituent, and R 10 and R 11 Each is independently selected from hydrogen, substituted or unsubstituted alkyl, or carboxyl, and L2 is selected from one or more of single bond, substituted or unsubstituted alkyl, carbonyl, ester, oxygen, sulfone, and amide. R2 is selected from the structures shown in equation G and / or equation H: R4 is selected from straight-chain alkyl or branched alkyl with 1 to 18 carbon atoms, and x1 is an integer from 10 to 25. Preferably, R4 is selected from straight-chain alkyl or branched alkyl with 4 to 8 carbon atoms. R5 and R6 are each independently selected from straight-chain alkyl groups having 1 to 12 carbon atoms or branched alkyl groups, and y1 is an integer from 10 to 25. Preferably, R5 and R6 are each independently selected from straight-chain alkyl groups having 1 to 3 carbon atoms or branched alkyl groups. R3 is selected from the structures shown in equations XI-1 to XI-16 below:

17. An electrode sheet, characterized in that, The electrode coating includes the polyimide binder of claim 15 or 16, or the polyimide binder prepared according to the preparation method of the polyimide binder of any one of claims 1-14.

18. The electrode sheet according to claim 17, characterized in that, The electrode sheet includes a positive electrode sheet.

19. A battery, characterized in that, Includes the electrode sheet as described in claim 17 or 18.

20. A battery pack, characterized in that, It includes at least two batteries as described in claim 19 that are interconnected.

21. An electrical appliance, characterized in that, Includes the battery of claim 19 or the battery pack of claim 20.